A infância de cristo em Ednotationes et meditationes in Euangelia do Padre Jerónimo - João Carlos Serafim (Universidade do Porto, 2010)
D. Vasco Luís da Gama (1612-1676), 1st Marquis of Niza, was one of the first lords that, in the mid 17th Century, decided to create a public library that would impress Lisbon. Among the many books that were ordered and suggested is the work of Priest Jerónimo Nadal – Adnotationes et meditations in Evangelia (1594) – already considered a iconographic treasure in its time… The images of childhood – noted and meditated upon… - analysed in this work demonstrate well the virtuousness of the Jesuit apologetic style of the time. Nadal’s work was responsible for establishing a rhetoric, of materializing a paideia which was later greatly cultivated.